The Effectiveness of Convalescent Plasma for the Treatment of Novel Corona Virus Disease 2019: A Systematic Review and Meta-Analysis - Cao, Huiling; Ming, Li; Chen, Long; Zhu, Xingwang; Shi, Yuan (Frontiers in Medicine, 2021)
Background: Coronavirus disease 2019 (COVID-19) sweeping across the world has created a worldwide pandemic. Effective treatments of COVID-19 are extremely urgent. Objective: To analyze the efficacy and safety of convalescent plasma on patients with COVID-19. Methods: All the relevant studies were searched from PubMed, EMBASE，Cochrane library, Scopus, Web of Science, CBM, CNKI, Wan fang, VIP ,Medrxiv,Biorxiv and SSRN on 19th July 2021. PICOS criteria were as follows: (P) the study interests human subjects with infection of COVID-19. (I)The intervention of interest was convalescent plasma(CCP) (C)Comparator treatments contained placebo, sham therapy, standard treatment. (O) The primary outcome were mortality rates by novel coronavirus. The secondary outcomes included the incidence of serious adverse events, the rate of ICU admission and mechanical ventilation, the length of hospital stay, duration of mechanical ventilation and ICU stay,the antibody levels, inflammatory factor levels and viral loads.(S)Only randomized controlled trials of CCP were included. Subanalysis, Quality assessment, sensitive analysis and publication bias was conducted by 2 reviewers independently. Results: 16 randomized control trails (RCTs) were included and enrolled a total of 16296 participants in this meta-analysis. The pooled data showed that no significant difference was observed in reducing the rate of overall mortality between convalescent plasma treatment group and placebo group(OR 0.96; 95%CI 0.90 to 1.03; p=0.30; I2 = 6%). According to the results of subgroup analysis, the severe or critical patients with convalescent plasma showed significant difference in reducing mortality of 28-day compared with placebo(OR 0.58, 95% CI 0.36 to 0.93,P=0.02,I2=0%). Convalescent plasma groups have a significantly shorter duration of mechanic ventilation compared to control group (weighted MD -1.00, 95% CI -1.86 to -0.14d P=0.02,I2=0%). No significant difference was observed in the length of hospital stay,the duration of ICU,the rate of ICU and mechanic ventilation.the There is no conclusive evidence about the safety of convalescent plasma. Conclusion:convalescent plasma can significantly reduce the mortality of 28-day in severe or critical COVID-19 patients and the duration of mechanical ventilation. However more evidence was needed to prove the safety of convalescent plasma.